2022
DOI: 10.1097/cce.0000000000000766
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of Recovery-Oriented Care Practices During Hospitalization for Sepsis

Abstract: Survivors of sepsis hospitalization are at high risk for postsepsis morbidity, readmission, and death, but these negative outcomes can be mitigated by receipt of recommended care practices. We sought to assess factors associated with the receipt of recommended recovery-oriented care practices during hospitalization for sepsis. We hypothesized that patients treated in the ICU may be more likely than ward-treated patients to receive recommended care practices given the increasing focus on survivorship in the cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…Meanwhile, multiple peridischarge and recovery-based practices, such as scheduling of timely outpatient follow-up, screening for new limitations, and provision of anticipatory guidance, were rated among the lowest of the practices evaluated. These findings are consistent with other studies showing low delivery of recovery-oriented practices and suggest that later sepsis care may be a key opportunity for improvement of hospital sepsis management (11, 12). Sepsis QI initiatives have traditionally focused on early recognition and treatment.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, multiple peridischarge and recovery-based practices, such as scheduling of timely outpatient follow-up, screening for new limitations, and provision of anticipatory guidance, were rated among the lowest of the practices evaluated. These findings are consistent with other studies showing low delivery of recovery-oriented practices and suggest that later sepsis care may be a key opportunity for improvement of hospital sepsis management (11, 12). Sepsis QI initiatives have traditionally focused on early recognition and treatment.…”
Section: Discussionsupporting
confidence: 92%
“…A retrospective cohort of sepsis survivors ( 7 ) found that 62% of patients received medication optimization (vs 68.2% “always/nearly always” in our study), and 58% had documented care alignment discussions (vs 50.0% “always/nearly always”). Watson et al ( 10 ) also reported high adoption of medication optimization and limited implementation of sepsis education and mental health evaluation. Our work adds to the growing body of evidence demonstrating variable implementation of best practices for sepsis recovery and newly demonstrates that these gaps in care are seen across hospitals with high and low sepsis survival rates.…”
Section: Discussionmentioning
confidence: 99%